Synthesis and reactivity of rhenium carbonyl complexes - Cuadros Alcivar, Elián Estenio (2025)
Recently, extensive studies have been conducted on the coordination chemistry of ligands with phosphinoyl groups and rhenium carbonyl precursors, leading to the formation of metal complexes with diverse nuclearity. Consequently, the reaction of halogenopentacarbonylrhenium(I) [ReX(CO)5]; X = Cl, Br with the ligand 2-bromo6-diphenylchalcogenophosphinoylpyridine, Br(C5H3N)P(Se)Ph2, was investigated in the presence of tertiary phosphines (PPh3 and P(p-Tol)3) through a one-pot reaction at toluene reflux to produce [ReX(CO)3L{κ-Se(Br(C5H3N)P(Se)Ph2)}]; X = Br, L = PPh3 (3a); X = Br, L = P(p-Tol)3 (3b); X = Cl, L = PPh3 (4a); X = Cl, L = P(p-Tol)3 (4b) complexes, in which the ligand is coordinated through the chalcogen. The new complexes were characterized using standard spectrometric and spectroscopic techniques (FTIR, NMR, MS). Furthermore, the reactivity study [ReBr(CO)5] with the sulfur-containing ligand Br(C5H3N)P(S)Ph2 was carried out in the presence of triphenylphosphine (PPh3), but no complexes were obtained due to the low nucleophilic power of sulfur.